Accurate circuit models for the analysis of stacked metal gratings - Medina, Francisco; Molero, Carlos; Rodriguez-Berral, Raul; Mesa, Francisco (Conference proceedings (International Conference on Mathematical Methods in Electromagnetic Theory. Print), 2016)
Stacked periodic planar structures have been a continuous subject of research interest due to their ability to control the polarization, transmission, reflection, and absorption of electromagnetic waves. The scattering of plane waves by one-dimensional (1-D) and two-dimensional (2-D) arrays of metal patches (or apertures) can be accurately modeled using suitable equivalent circuits. The structures obtained by stacking periodic systems of this type can easily be modeled using transmission line sections to account for the dielectric region between the periodic surfaces. However, this task is not straightforward if the separation between the periodically structure surfaces is electrically small. This contribution will describe a methodology to obtain valid and accurate circuit models for tightly spaced periodic arrays of apertures. The proposed theory allows for the modeling of devices that have attracted a lot of attention in recent years, such as the fishnet structures employed to obtain an effective negative index of refraction.